Gender, financial literacy, internal control locus, and economic well-being: The employee viewpoint - Bram Hadianto; Ana Mariana (Owner : Riset dan Jurnal Akuntansi, 2023)
Economic well-being is related to financial freedom and become a vital topic for employees to perform well in the workplace. Hence, this study examines and analyzes the determinants. Based on prior works, they are gender, financial literacy, and internal control locus. The population is 500 employees of PT. Sinar Indogreen Kencana in Sidoarjo. Furthermore, this study utilizes the Slovin formula with a 10% margin of error to search for the sample size. After calculation based on this formula, its size is 222 employees. For taking them, this study used a simple random technique. Considering this number, the researcher utilizes a covariance-based structural equation model, preceded by validity and reliability examinations and goodness of fit detection. After passing the related tests and detection, this study examines the planned hypotheses and concludes that males have better economic well-being than females. Besides, financial literacy and locus of control have a positive effect on financial well-being. Also, the contribution of these four factors to explaining economic well-being is high, demonstrated by an R-square of 0.821.